EFFECT COMPENSATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PT. CIREBON NOBLE POWER ARTERIA MINE PRODUCTION PART - Hidayah, Nurul; Solehudin, Ade; Wibowo, Sandi Nasrudin (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2022)
HR has a major contribution when determining the development of a company. The method used in this research is a quantitative method to understand the impact of compensation and job satisfaction on staff performance at PT. Cirebon noble power artery. The population of this research is the permanent staff of PT. Arteria Daya Mulia Cirebon, with a total of 55 employees, analyzed the data using multiple linear regression. The results of the research show that partial compensation has a good and significant impact on staff performance. Job satisfaction has a good and significant impact on staff performance. Meanwhile, compensation and job satisfaction have a good and significant impact on staff performance, which is shown using the calculated F value Ftable which is 176,727 3,18 and significant 0.000. The ability of compensation variables and job satisfaction variables in expressing staff performance is 86.7% , the remaining 1.33% is influenced by factors that have not been studied. With this multiple linear regression equation Y = 2506 0.130 0.854